Research progress on location privacy-preserving techniques - Sheng WAN; Feng-hua LI; Ben NIU; Zhe SUN; Hui LI (Tongxin xuebao)
While providing plenty of convenience for users in daily life, the increasingly popular location-based ser-vice(LBS) posed a serious threat to users' privacy. The research about privacy-preserving techniques for LBS is becoming a hot spot, and there are a large number of research results. First, background information of privacy protection for LBS was introduced, including application scenarios of LBS, the LBS framework, objects of privacy protection and system architectures of privacy protection. Second, adversary models and metrics for privacy protection in LBS was discussed. Third, four types of privacy-preserving techniques based on generalization and obfuscation for LBS were analyzed and summarized thoroughly. Finally, the potential research directions for privacy-preserving techniques for LBS in the future were shown.